The Effect of Lunar Phase on Squid Catches Using Flashing Led Lights: Pengaruh Fase Bulan Terhadap Hasil Tangkapan Pancing Cumi-Cumi Menggunakan Lampu Led Berkedip - Handoko Palawe; Frangky Kaparang; Alfred Luasunaung; K.W.A Masengi; Lefrand Manoppo; Deiske. A Sumilat (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2021)
The use of flashing LED lights on squid fishing rods to catch squids is still used by fishermen without concerning the lunar phase due to a lack of knowledge about the influence of the lunar phase on the squid catch. This study was conducted to 1. determine the effect of the lunar phase on the catch of squid using fishing rods, 2. compare the number of catches obtained using blue and white LED flashing lights. This experimental study was conducted using a Randomized Block Design (RBD). Data regarding squid catches (per squid) using blue and white LED lights were collected in 4 lunar phases. Data were then analyzed using variance analysis (ANOVA). Results showed that the lunar phase significantly affected the squid catching using fishing rods at a significance level of 0.05 (5%). Catches were significantly different in the new moon, first quarter, full moon, and third quarter phases. A higher number of catches was obtained in the third quarter phase compared to other phases. ANOVA test indicated a strong significant effect of the use of LED on the catch at a significant level of 0.05 (5%). The use of flashing blue LED resulted in a higher number of squid catches than white LED since squids were more attracted by blue light than white light.